2005
DOI: 10.1007/s10238-005-0072-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of cigarette smoking on lipid peroxidation, glutathione enzymes and paraoxonase 1 activity in healthy people

Abstract: The purpose of this study was to examine the effect of different levels of cigarette smoking on lipid peroxidation, glutathione enzymes and paraoxonase 1 (PON1) activity in a healthy population. The study included 130 subjects who were classified as mild (20 cigarettes daily, Group III, n=33) and never smokers (controls, Group IV, n=32). Malondialdehyde (MDA) levels, PON1 and erythrocyte glutathione enzyme activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 37 publications
6
53
1
1
Order By: Relevance
“…Guentsch et al (23) and Akalın et al (24) reported that MDA levels increased in the saliva of smokers versus nonsmokers and these findings were in concordance with those reported by some previous studies in venous blood erythrocyte/serum/plasma (22,(25)(26)(27). Our findings support these results.…”
Section: Discussionsupporting
confidence: 93%
“…Guentsch et al (23) and Akalın et al (24) reported that MDA levels increased in the saliva of smokers versus nonsmokers and these findings were in concordance with those reported by some previous studies in venous blood erythrocyte/serum/plasma (22,(25)(26)(27). Our findings support these results.…”
Section: Discussionsupporting
confidence: 93%
“…In non-schizophrenic smokers, MDA also increases as a product of this oxidative stress (Altuntas et al, 2002;Ozguner et al, 2005;Solak et al, 2005). However, the lower MDA levels in schizophrenic smokers suggests that tobacco smoke increases the activity of these antioxidant enzymes more than is needed to simply counteract the peroxidation effects of tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine in quantities similar to those in cigarette smoke can induce oxidative stress, as shown in vitro and in vivo (Solak et al, 2005). Increased lipid peroxidation occurs in Chinese hamster ovary cells (Yildiz et al, 1998) and pancreatic tissue of rats (Wetscher et al, 1995) that are incubated with nicotine.…”
Section: Introductionmentioning
confidence: 96%
“…As dyslipidemia, including hypertriglyceridemia and hypo-HDL-cholesterolemia, is important in the pathogenesis of atherosclerosis, smoking may accelerate the development of CVDs indirectly via its detrimental effects on serum lipid profiles. Smoking was also reported to induce qualitative changes in serum lipids (28)(29)(30). Excess free radicals and oxidants present in cigarette smoke, as well as endogenously produced oxidants and radicals, enhance the pro-oxidative environment (6,29).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking was also reported to induce qualitative changes in serum lipids (28)(29)(30). Excess free radicals and oxidants present in cigarette smoke, as well as endogenously produced oxidants and radicals, enhance the pro-oxidative environment (6,29). It was suggested that peroxynitrite is significant in the oxidative modification of plasma LDL induced by smoking (30).…”
Section: Discussionmentioning
confidence: 99%